Distribusi kanker dan analisis faktor yang memengaruhi: analisis data Indonesia family life survey tahun 2014 (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: This study was to identify distribution of cancer and factors associated using Indonesia family life survey in 2014.Methods: This was descriptive study with cross sectional design using secondary data. The source of the data was Indonesia Family Life Survey (IFLS 5) in 2014. The total of study participants were 34,240 respondents obtained by inclusion and exclusion criteria. Bivariate analysis used chi-square test and multivariate analysis used logistic regression.Results: The best model in multivariate analysis showed that sex (OR=5.34; 95% CI=3.64-7.83), age (OR=5.41; 95% CI=2.88-10.13), consumption vegetable and fruits (OR=0.74; 95% CI=0.56-0.99), education level (OR=0.38; 95% CI=0.26-0.56), and overweight (OR=0,58; 95% CI= 0,36-0,94) were statistically related to cancer.Conclusions: The prevalence of cancer was 0.63%, the respondents diagnosed with cancer wre 205 respondents with the most types of cancer was breast cancer 35.61% followed by ovarian cancer with a proportion of 18.05%. Sex, age, and education and consumption of fruits and vegetables were significantly associated with cancer.